Observation of Zenneck-Like Waves over a Metasurface Designed for Launching HF Radar Surface Wave - Florent Jangal; Nicolas Bourey; Muriel Darces; François Issac; Marc Hélier (International Journal of Antennas and Propagation)
Since the beginning of the 20th century a controversy has been continuously revived about the existence of the Zenneck Wave. This wave is a theoretical solution of Maxwell’s equations and might be propagated along the interface between the air and a dielectric medium. The expected weak attenuation at large distance explains the constant interest for this wave. Notably in the High Frequency band such a wave had been thought as a key point to reduce the high attenuation observed in High Frequency Surface Wave Radar. Despite many works on that topic and various experiments attempted during one century, there is still an alternation of statements between its existence and its nonexistence. We report here an experiment done during the optimisation of the transmitting antennas for Surface Wave Radars. Using an infrared method, we visualize a wave having the structure described by Zenneck above a metasurface located on a dielectric slab.